The Impact of Packaging Type and Branding on Consumer Quality Perception and Preferences - Sostar, Marko; Korov, Tomislav; Pjero, Elenica (International Review of Management and Marketing, 2025)
This study examines the impact of packaging type and branding on consumer perceptions of quality and preferences in the context of food products. The research involved 310 participants who evaluated the same product (beer) in different types of packaging (glass, plastic, metal) and in branded and non-branded versions. Data were collected through a survey questionnaire, and the analysis was conducted in JASP using repeated measures ANOVA. The results revealed that packaging type has a statistically significant impact on quality perception and consumer preferences, with glass perceived as the highest-quality material, while plastic received the lowest ratings. Branded products were consistently rated higher than non-branded ones across all packaging types. The interaction between packaging and branding was also significant, with branded products in glass packaging receiving the highest ratings. These findings highlight the critical role of packaging design and branding strategies in shaping consumer perceptions and provide valuable guidance for manufacturers in optimizing product presentation and market positioning.